2021
DOI: 10.1021/acs.jproteome.1c00766
|View full text |Cite
|
Sign up to set email alerts
|

MSTopDiff: A Tool for the Visualization of Mass Shifts in Deconvoluted Top-Down Proteomics Data for the Database-Independent Detection of Protein Modifications

Abstract: Top-down proteomics analyzes intact proteoforms with all of their post-translational modifications and genetic and RNA splice variants. In addition, modifications introduced either deliberately or inadvertently during sample preparation, that is, via oxidation, alkylation, or labeling reagents, or through the formation of noncovalent adducts (e.g., detergents) further increase the sample complexity. To facilitate the recognition of protein modifications introduced during top-down analysis, we developed MSTopDi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…For quality control, deconvoluted (FlashDeconv) spectra were inspected by MSTopDiff, which is a tool for the database-independent detection of modifications in top-down data (Figure S6). In both workflows, no indications for artificial modifications introduced during sample preparation (e.g., over- or underalkylation) or for SDS adducts (due to incomplete SDS removal) were found. This further demonstrates that SDS can be efficiently removed using the PEPPI-AnExSP protocol …”
Section: Resultsmentioning
confidence: 95%
“…For quality control, deconvoluted (FlashDeconv) spectra were inspected by MSTopDiff, which is a tool for the database-independent detection of modifications in top-down data (Figure S6). In both workflows, no indications for artificial modifications introduced during sample preparation (e.g., over- or underalkylation) or for SDS adducts (due to incomplete SDS removal) were found. This further demonstrates that SDS can be efficiently removed using the PEPPI-AnExSP protocol …”
Section: Resultsmentioning
confidence: 95%
“…The isoelectric point and the grand average of hydropathy (GRAVY) score of the proteoforms (without considering modifications) were calculated using Pyteomics . For quality control, all raw data were assessed using MSTopDiff (v1.0.0), which allowed for the database-independent detection of modifications in deconvoluted top-down data . Besides previously described artificial modifications (oxidation or formylation introduced during sample preparation) or biological modifications (phosphorylation, acetylation), no prominent unexpected mass shifts were observed (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…elegans sample was subjected to GELFrEE separation and subsequently analyzed via RP–LC–MS/MS using EThcD and CID. In our experiment, significant under- and/or overlabeling could not be detected, neither by manual inspection of the MS1 trace nor by systematic evaluation via MSTopDIFF (Figure S15). Our findings align with the experiments conducted by Liu et al who employed reductive dimethylation for quantification of intact proteins and reported high labeling efficiencies as well …”
Section: Resultsmentioning
confidence: 61%